POTENTIAL DESCRIPTION OF alfa -PARTICLES SCATTERING ON 6Li AND 7Li ISOTOPES - Burkova N.А.; Zhusupov, M.A.; Kabatayeva, R.S. (Recent Contributions to Physics, 2011)
Phases of -particles elastic scattering on 6Li and 7Li lithium isotopes are calculated. Potential interaction effects in the photonuclear channels are estimated.